Influence of Knowledge Level about Anemia and Menstrual Patterns on Adherence to Consumption Iron Supplement in Adolescents at A Public Senior High School in Magelang - Annisa Nabila Nugraheni; Elmiawati Latifah; Ratna Wijayatri (Pharmacon: Jurnal Farmasi Indonesia, 2023)
Anemia is a health problem in all age groups, from toddlers to old age. Adolescent girls are prone to anemia due to their monthly menstrual cycle, so iron supplementation is needed, one of which is Supplementary Blood Tablets. This study was to find out the influence of  the knowledge level about anemia and menstrual patterns on compliance of iron supplement consumption in adolescents at a public senior high school in Magelang. This analytical research was carried out in December 2022 using a survey method with a research instrument in the form of a questionnaire in the form of a Google Form which was distributed via the Whatsapp application. The sampling technique was probability sampling in the form of proportionate stratified random sampling with the inclusion criteria for young women, active high school students, menstruating, aged 15-18 years, as well as exclusion criteria for high school students who were not willing to participate as research respondents. A population of 500 students came from grades 10, 11, and 12 and was calculated using the slovin formula (e = 5%) to obtain a sample of 250 students. The research questionnaire was adapted from four different studies with a total of 39 question items that had been tested for instrument validity content using the Aiken index calculation, and all questionnaire items tested valid with results 0.8. The results showed that young women at a public senior high school in Magelang had a "good" level of knowledge about anemia with a percentage of 58.8%, 85.2% experienced normal menarche, 77.2% had normal menstrual cycles, 71.6% experienced dysmenorrhea, and adherence to iron supplement consumption was low. 84.4% of respondents "didn't comply" and 66.4% "forgot to consume" so it is necessary to increase socialization from health and education agencies regarding the importance of consumming iron supplement in adolescents . While the SPSS version 26 analysis was carried out using normality and homogeneity tests, non-parametric statistical tests were used with chi-square test yielded P values of 0.6240.05 and 0.2750.05, meaning that the level of knowledge about anemia and menstrual patterns had no effect on the adherence to iron supplement consumption in adolescents at a public senior high school in MagelangKeywords: knowledge of anemia, menstrual patterns, consumption compliance, iron tablets,  young women